Community–clinic linkages: qualitative provider perspectives on partnering with community health representatives in Navajo Nation. Issue 2 (12th February 2020) - Brown, Christian; Lalla, Amber; Curley, Cameron; King, Caroline; Muskett, Olivia; Salt, Shine; Ray, Kathy; Begay, Mae-Gilene; Nelson, Adrianne Katrina; Shin, Sonya
Abstract : Objective: To understand providers' opinions about the Community Outreach and Patient Empowerment (COPE) Project designed to strengthen Navajo Community Health Representative (CHR) outreach to individuals living with diabetes. Design: This was a qualitative study nested within a larger evaluation of a programme intervention. Setting: The study took place in Navajo Nation and evaluated a programme initiative designed to strengthen collaboration between CHRs and clinic-based healthcare providers and provide structured outreach to individuals living with diabetes in Navajo Nation. The CHR Programme is a formal community health worker programme that exists in most tribal healthcare systems across the USA. Participants: Healthcare providers involved in the programme took part in one-on-one interviews. Analysis: We used thematic analysis for this study. A team of three study staff used open-coding to create a codebook. Coded material were summarised and patterns were identified and tied into a narrative using concept mapping. The study design and instrument construction were guided by a Community Health Advisory Panel. Results: A total of 13 interviews were completed. Providers acknowledged CHRs as an asset to the clinical team and were enthusiastic about the COPE coaching materials, mentioning they provided a consistent message to CHRs and the community. Providers that led COPE trainings with CHRs valued the face-to-face time and opportunity to build relationships. Providers (n=4) supported CHRs' access to electronic health record to record patient visits and streamline referrals. Among their requests were having designated personnel to manage referrals with CHRs and a formal system to record modules CHRs have completed. Conclusion: Providers participating in COPE activities valued the work of CHRs and endorsed further strengthening relationships and communication with CHRs. Healthcare programmes should consider systems changes to integrate community health workers into clinic-based teams. Trial registration number: NCT03326206 ; Results.